KONSELING INDIVIDU UNTUK MENINGKATKAN KEMANDIRIAN SANTRI DI SPM ULA I’DAAD SHIGOR DAARUL QUR’AN - Gian Rusdiyana; Nur Azmi Wiantina; Pebrisa Amrina (IKIP Siliwangi, 2026)
This study aims to enhance the independence of early-age students (santri) at the Tahfizh Shigor Daarul Qur’an Islamic Boarding School through individual counseling services utilizing positive reinforcement techniques. The research is motivated by the low level of independence observed among students, as indicated by their reliance on others for completing daily tasks. Contributing factors include permissive parenting styles, lack of early training, and unfamiliarity with the boarding school environment. This study employs a qualitative approach with a case study method, involving two students identified as having low levels of independence. Data were collected through observation, interviews, and documentation. The counseling process involved the application of positive reinforcement in the form of social rewards such as praise and applause, alongside a psychodynamic approach to explore the psychological roots of the students’ behavior. The results indicate a significant improvement in the students’ independence, as reflected in their ability to complete tasks on their own, increased intrinsic motivation to learn, and freedom in setting learning goals without dependence on others. Therefore, individual counseling combined with positive reinforcement proves to be an effective strategy in fostering and strengthening student independence in the pesantren environment.